Predictors of social skills and behavioral problems in children - Bolsoni-Silva, Alessandra Turini [UNESP] (2018)
Social skills and behavioral problems are influenced by multiple variables. Objective was to compare groups of children distinguished by social skill deficits and behavioral problems, according to sociodemographic variables, educational practices, family environment resources, and indicators of maternal depression, verifying the predictive value of those variables. Participants were 151 mothers of children, and data were compared and treated by binary logistic regression. On the regression models, the following influences were observed: a) in case of social skills related to the positive and negative educational practices - behavioral problems and low income; b) in case of behavioral problems related to the negative practices - child social skills, mother's schooling, mother's marital state and child's gender. In comparisons, environmental resources and maternal depression differentiated the groups. Simultaneous evaluation of the variables emphasizes intersections and differences of the constructs.